The Relationship between Epigenetics and Lifestyle in Homosexuality - HÜSEYIN ÇAKSEN (Pakistan Journal of Medical & Health Sciences, 2025)
Homosexuality is a pattern of sexuality in which sexual behavior and thinking are directed towards people of the same sex. Although the Ibrahamic religions of Islam, Christianity, and Judaism prohibit homosexuality and teach that such behavior is sinful, male homosexuality, in particular, has been reported in many different cultures and historical eras. Lut1 (Alayhi As-Salam [AS]), nephew of the Prophet Ibrahim2 (AS), was sent as a prophet to the cities of Sodom and Gomorrah in the 22nd-20th centuries before Christ. Male homosexuality was very common in the tribe to which Lut (AS) was sent as a prophet. Lut (AS) conveyed the commands of Allah to people in order to make them give up homosexuality and make them follow him. Because the people continued their bad habits despite all the warnings of Lut (AS), Allah sent down torment on them. Allah turned (the cities) upside down, and rained down on them brimstones hard as baked clay, spread, layer on layer1,3. To the best of our knowledge, this is the first documented report of homosexuality in human history.